The Correlation between Students’ Habit of Watching English Movies and Their Speaking Ability - Frans, Nofry -; Rotty, Kevin Marchelino; Wahani, Vera (DIDASCO, 2025)
Abstract This study aimed to explore whether there is a connection between students' habit of watching English movies and their speaking skills. Conducted with 8th-grade students at SMPN 2 Airmadidi during the 2023/2024 academic year, it involved 64 participants from B and C classes. The research utilized descriptive mean analysis and Pearson Product Coefficient Correlation to interpret the findings. Results indicated that students frequently watched English movies (average score of 4.25) and possessed high speaking ability (average score of 4.23). However, no significant correlation was found between these two factors (p = 0.129, r = 0.192), suggesting that other elements may play a more critical role in speaking proficiency. Despite the lack of a strong link, the study highlights the potential benefits of watching English movies as part of a broader language-learning strategy, contributing to motivation, cultural awareness, and overall language acquisition. The findings provide valuable insights into the relationship between movie-watching habits and speaking skills, emphasizing the need for diverse and multifaceted approaches in language education. Keywords: Habit, Speaking Ability, Watching English Movies.